Development of a quizmaker ispring approach assessment instrument to measure understanding of student concepts - Desfion Mayuri; Prima Aswirna; Hurriyah Hurriyah (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2021)
The purpose of this study is to produce a valid, practical and effective Ispring Quizmaker Application Assisted Instrument. The development model of the assessment instrument used is the Plomp model which includes three stages of development, namely: preliminary research (preliminary research), the development phase or prototype (development of prototypephase), and the assessment phase (Assessment phase). The results of the study have produced a valid, practical and effective Ispring Quizmaker application-assisted assessment instrument. The instrument is valid both in terms of material, construction, media and language with an average value of 78.76% with a very valid category. The practicality of the media has an average value of 92.06% with a very practical category, while for the effectiveness of understanding physics concepts based on questions per item of indicators understanding the concept of 65, 11% with the effective category.